Changes in the Porous Texture of Hydrous Ferric Oxide on Adsorption of Transition Metal Ions: Adsorption Mechanism - L.B. Khalil; M.N. Alaya; N.Sh. Petro; R.M.M. Abo Elenein (Adsorption Science & Technology)
In general, it was found that loading hydrous ferric oxide (HFO) with transition metal ions led to a decrease in both the internal surface and external surface area. The micropore volume in the microporous samples (obtained by heating the oxide at 50°C and 200°C) and the total pore volume in both samples and in the mesoporous sample (obtained by heating the oxide at 400°C) also decreased. The mean pore radius, however, appeared to be little altered in all the samples. The observed effects cannot be interpreted on the basis of the adsorption of unhydrated transition metal ions, nor by assuming precipitation of these ions as hydroxides inside the pores. The only other possibility was the assumption that the adsorption of these ions was accompanied by the adsorption of relatively more strongly adsorbed water (not removed during evacuation of the samples) and/or the transformation of water already present in the oxide to strongly adsorbed water. This conclusion was confirmed by comparing the water loss at 100°C and 200°C in the original and metal-loaded HFO samples.